Peran Pemerintah Daerah, Industri, Dan Masyarakat Dalam Pengelolaan Kepariwisataan Berkelanjutan - Agus Muriawan Putra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
The purpose of this study is to determine the role of the community, industry, and local government in the management of tourism and culture, so that management and development are sustainable as a means for community welfare, the revolving wheel of people's economy, and maintaining the preservation of nature, culture, and spirits of an area. Data were collected using field study methods, and literature studies, and analyzed using qualitative descriptive methods. The results of this study are: (1) the participation of the community, industry, and local government in the management of tourism and culture; and (2) relating to the development of quality, sustainable, and balanced tourism and culture.